IMPROVING STUDENTS’ READING COMPREHENSION THROUGH SQ3R (SURVEY, QUESTION, READ, RECITE AND REVIEW) TECHNIQUE - Gian Reka Anjuni; Roby Cahyadi (PROJECT (Professional Journal of English Education), 2019)
This research entitled “Improving Students’ Reading Comprehension Through SQ3R Technique”. This research has purpose to figure out the use of SQ3R strategy in improving students’ reading comprehension. The population of this research is students of SMA Negeri 1 Cipongkor including eleventh grade of IPS class and IPA class. The number of population is 60 students. The sample of this research is only one class that is IPS class consists 30 students. The quantitative research method is used in this research, and specifically the one group pre-test post-test design as research design. The instrument of this researches is pretest and posttest and the writers also use t-test formula for collecting data.  The result of the research shows that tobs is 2.42, the ttable with degrees of freedom (df) 29 and level of significance at 0.05 was 1,69. Based on the data, the t-test result was 2.42, it was higher that t-table (2.42 > 1.69). It means the alternative hypothesis was accepted. According to the data analysis which is collected, it can be concluded that the test is reliable. And the research showed that teaching students’ reading comprehension using SQ3R technique is very useful. That is why, the SQ3R strategy is suitable in improving students’ reading comprehension.Keywords:  Reading, Reading Comprehension, SQ3R Strategy